Articulating the conceptual and the discursive dimensions of figurative language in argumentative texts - Vereza, Solange Coelho (2010)
One of the greatest challenges of recent studies on metaphor in discourse is to articulate, systematically, the discursive with the cognitive dimensions of figurative language. Within this perspective, the aim of this paper is to present and to discuss an analytical approach to the study of metaphor in argumentative texts which aims at observing how metaphoricity might emerge and be explored discursively, through underlying conceptual metaphors and textually dependent mappings. To this end, a unit of analysis is proposed: the metaphor niche.